2013
DOI: 10.1016/j.pscychresns.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal fusiform activation during emotional-face encoding assessed with functional magnetic resonance imaging

Abstract: This fMRI study shows that, compared to healthy subjects, children and adults with bipolar disorder (BD) exhibit impaired memory for emotional faces and abnormal fusiform activation during encoding. Fusiform activation abnormalities in BD were correlated with mania severity and may therefore represent a trait and state BD biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Further, the reduced corpus callosum volume and white matter integrity aligns with twin studies suggesting genetically influenced alterations of this structure in BP 88,89 . Gray matter reduction in temporal structures, including the superior temporal sulcus (STS) and the lingual and fusiform gyri, are noteworthy given the involvement of these structures in facial emotion identification, a process impaired in BP individuals and adolescents at high-risk 9094 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, the reduced corpus callosum volume and white matter integrity aligns with twin studies suggesting genetically influenced alterations of this structure in BP 88,89 . Gray matter reduction in temporal structures, including the superior temporal sulcus (STS) and the lingual and fusiform gyri, are noteworthy given the involvement of these structures in facial emotion identification, a process impaired in BP individuals and adolescents at high-risk 9094 .…”
Section: Discussionmentioning
confidence: 99%
“…The first-level literature search yielded 1,181 unique published articles with 155 meeting initial inclusion criteria, including 3 four-group studies with separate BD-youth and BD-adult participant groups 16,17,19 (Figure 1). …”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, only four currently-published task-related functional magnetic resonance imaging (fMRI) studies have directly compared BD-youths and BD-adults in the same study 1619 . Specifically, Kim (2012) found that BD-youths had greater amygdala activation during emotional face recognition than BD-adults 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies can help elucidate such processes by identifying abnormal functioning in neural circuitries supporting information processing domains known to be aberrant in individuals with established bipolar disorder, such as face emotion processing. For example, youth and adults with bipolar disorder are impaired in both memory for emotional faces (Dickstein et al, 2007;Adleman et al, 2013) and identification of facial emotional expressions (Rich et al, 2006;Guyer et al, 2007). Comparing BO and NBO in neuroimaging studies of face emotion processing circuitry may thus help identify biomarkers reflecting risk for, or protection against, bipolar disorder specifically.…”
Section: Introductionmentioning
confidence: 99%